2006
DOI: 10.4049/jimmunol.177.7.4376
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of CTLA-4 on CD4+CD25+ Regulatory T Cells Abrogates Their Function In Vivo

Abstract: Naturally occurring CD4+ TR cells that express CD25 and the transcription factor FoxP3 play a key role in immune homeostasis preventing immune pathological responses to self and foreign antigens. CTLA-4 is expressed by a high percentage of these cells, and is often considered as a marker for TR in experimental and clinical analysis. However, it has not yet been proven that CTLA-4 has a direct role in TR function. Using a colitis transfer model, we previously showed that anti-CTLA-4 mAb treatment abrogates supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
309
8
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 380 publications
(341 citation statements)
references
References 62 publications
13
309
8
5
Order By: Relevance
“…However, unlike the protection afforded by wild-type T reg cells, disease protection mediated by CTLA-4-deficient T reg cells is dependent on IL-10 (ref. 43). That in vivo finding is consistent with in vitro analyses showing that CTLA-4-deficient T reg cells are distinct from wild-type T reg cells in the dependency of their suppressive function on TGF-β 42 .…”
Section: T Reg Cells Alter Apcssupporting
confidence: 79%
See 1 more Smart Citation
“…However, unlike the protection afforded by wild-type T reg cells, disease protection mediated by CTLA-4-deficient T reg cells is dependent on IL-10 (ref. 43). That in vivo finding is consistent with in vitro analyses showing that CTLA-4-deficient T reg cells are distinct from wild-type T reg cells in the dependency of their suppressive function on TGF-β 42 .…”
Section: T Reg Cells Alter Apcssupporting
confidence: 79%
“…Control of more aggressive forms of disease induced by memory T cells or pathogenic bacteria and reversion of established disease requires IL-10 in addition to CTLA-4 and TGF-β. In contrast, in the absence of one of the suppressive mechanisms (such as CTLA-4), T reg cells rely more on alternative suppressive functions such as IL-10 and TGF-β in vitro and in vivo 42,43 . Thus, it is possible that T reg cellmediated control of IBD, a disease at the highly inflammation-prone mucosal surface, may require a wider array of suppressive mechanisms operating in synergy and thus that the presence of IL-10, TGF-β, CTLA-4, and IL-35 as well as IL-2 deprivations are necessary for complete protection.…”
Section: The 'Big Picture'mentioning
confidence: 99%
“…Treg can interact with other immune populations via soluble factors and/or via cell-contactdependent mechanisms. Whereas in vivo studies have suggested a major role for soluble factors, such as IL-10 [41], TGF-b [42], or IL-35 [43], most in vitro experiments described a cell-contactdependent mechanism, involving CTLA-4 [44,45], GITR [46], Perforin [33], or Granzyme B [34]. Our data suggest that Perforin/ Granzyme-induced apoptosis does not play a major role in Tregmediated suppression of mouse gd-T-cell activity.…”
Section: Discussionmentioning
confidence: 51%
“…This suggests that CTLA-4 controls TCR accumulation/retention in membrane microdomains thereby blocking formation of a stable immunological synapse and downstream signalling events. In addition, CTLA-4 is constitutively expressed on the majority of Treg, and plays an important role in their function [9][10][11][12]. The relative contribution of CTLA-4 to the intrinsic regulation of responder T-cell activation and Treg function remain unclear.…”
Section: Introductionmentioning
confidence: 99%